Rappresentazioni dell'ebraismo nella letteratura eresiografica musulmana: Nāši' al-Akbar, Ibn Ḥazm e Šahrastānī - Colombo, Valentina (Annali di storia dell'esegesi, 2000)
If there is evidence of the presence of Jews in the Arab Peninsula from pre-Islamic times, and if several studies have been devoted to the relationships between Moslems and Jews, the representation of Judaism in Islamic literature on heresy has received less attention. In the present article this latter aspect is analyzed starting from the work of three heresiographers: Nasvhi’ al-Akbar, Sahrastani and Ibn Hazm. Nasvi’ al-Akbar is important because he is one of the first Moslem heresiographers, Sahrastani because he is the main representative of the genre, and Ibn H.azm of Cordoba because he had direct contact with the Jews of Spain. It is primarily the latter who has provided us with the most vivid picture of Judaism and the Jews in his Epistle against the Jew Ibn Naghrila, an epistle striking for its vehemence as well as for its final redemption of the Jews, in that they were a People of the Book.